Increasing Divergent Thinking Capabilities With Music-Feedback Exercise - Fritz, Thomas Hans; Montgomery, Max Archibald; Busch, Eric; Schneider, Lydia; Villringer, Arno (Frontiers in Psychology, 2020)
Divergent thinking is an essential aspect of creativity and has been shown to be affected both by music and physical exercise. Recent research has shown that making music and physical exercise can be combined so that physical exercise can be performed with simultaneous music-feedback. The present experiment tested the effects of making music and exercising on creativity. Measurements of divergent thinking were collected after (1) physical exercise, (2) making music with a knob setup or (3) making physical exercise with musical feedback (Jymmin). Results showed greater increases in divergent thinking scores following music feedback exercise compared to conditions of physical exercise, and musical agency. The data thus demonstrate that making music part of a physical exercise routine more strongly leads to the benefit of increased creative capacities. We discuss potential advantages of this effect as an intervention to increase tolerance for uncertainty in clinical populations and for athletes doing a music-feedback supported warm-up procedure for sports activities.